Kinerja Perawat dalam Kaitannya dengan Kepemimpinan dengan Kompensasi melalui Motivasi di Rumah Sakit X - Riyanto Prasetyo; Elsye Maria Rosa (Jurnal Admmirasi, 2020)
Nursing services make an important contribution in the quality of services in hospitals, so that every effort to improve the quality of services in hospitals must improve by improving the quality of nursing services, one of which is by improving the performance of nurses. Problems that arise based on a preliminary study conducted at the beginning of October 2016 at Hospital X, is still a problem of nurses who treat patients who experience an increase in nurses. Research Objectives: Knowing the influence of leadership in nursing environment on nurses 'motivation at Hospital X. Knowing the motivation of compensation in nursing environment on nurses' motivation at Hospital X. Knowing the effect of leadership in nursing on nurses at Hospital X. with cross sectional research design. Subjects in this study were nurses at Hospital X with a total sample of 70 people who were contacted by questionnaire instruments, while the research object was leadership, compensation, motivation, and performance of nurses at Hospital X. Processing data about this study using a computer program with SPSS 15.0 and using the F Test and t Test. Conclusion: After conducting an assessment of testing can prove the performance of nurses RS X need significant support by leadership, compensation through motivation.